Yield gaps and their determinates for wheat production in irrigated drylands for Egypt - Devkota Wasti, Mina; Omar, Mohie; Attaher, Samar; Govind, Ajit; Devkota, Krishna; Tesfaye, Kindie; Nangia, Vinay (International Center for Agricultural Research in the Dry Areas, 2024)
In Egypt, wheat (Triticum aestivum) plays a pivotal role in the country’s agricultural and economic landscape. It is the major component of the national diet and an essential contributor to food security. Its cultivation in the country has a rich history dating back to ancient times. The Nile Delta has always been an ideal location for wheat cultivation. Historically, Egypt was known as the “Breadbasket of the Roman Empire”, highlighting its crucial role in sustaining its population and neighbouring regions. In the country, compared to all crops, it is grown in the largest area (1.33 million ha) and the country produces 9.1 million tons of wheat (average productivity of 6.81 t ha-1) (Source: Economic Affairs Sector, Ministry of Agriculture and Land Reclamation, 2023). Compared to all crops, its cultivation area is increasing in the country. However, it is meeting 50% of the demand from the international market to fill the gap between production and consumption (5.86 million t, one of the top 10th largest importers), where the import value of wheat and wheat products was 2.49 billion USD in 2021 (FAOSTAT, 2023). In recent years (2018-2021), Egypt has shown prominence in reducing imports, where it imported 9.53 million tons wheat in 2021/2022 while it decreased by 17.5% (7.86 million tons) in 2022/2023 (Source: Agriculture Economic Research Institute (AERC). However, to reduce imports sustainably, the country might need to adopt both approaches, i.e., area expansion in New Land and sustainably closing the yield gap in the Old Lands. Adopting science-led demand-driven and sustainable (economic, environmental, and social) farming practices, including improved crop varieties and efficient agronomic management practices, is the key for the sustainable intensification of wheat production in both new and old lands. By implementing below climate-smart wheat production technology tailored to Egypt›s conditions, farmers can enhance their yields, contribute to the country›s demand, and support its agricultural growth.